The role of country by country reporting on corporate tax avoidance: Does it effective for the tax haven? - Lulus Kurniasih; Yusniyati Yusri; Fakarudin Kamarudin; Ahmad Fahmi Sheikh Hassan (Cogent Business & Management, 2023)
The study evaluates the direct and moderating influence of Country-by-Country Reporting (CbCR) regulation in deterring corporate tax avoidance of multinational corporation listed in Indonesia Stock Exchange. The Indonesian CbCR stated in the regulations enacted by government of Indonesia namely Ministry of Finance Regulation no. 213/PMK/2016 (MoFR 213/PMK/2016) and Directorate General of Taxes Regulation no. 29/2017 (DGTR-29/2017). We use panel data in this study. Data is collected from the financial statements of 166 multinational companies listed in Indonesia Stock Exchange from 2010 to 2019, resulting in final sample of 1315 observations. Pooled OLS regression is used to test the hypotheses. The results show that the CbCR regulation issued by the government has significant negative impact on corporate tax avoidance measured by abnormal related party transaction. Thus, it effectively deterred multinational companies' corporate tax avoidance. Furthermore, we examine the influence of tax haven affiliation on corporate tax avoidance which provides evidence that companies with tax haven affiliation have higher level of corporate tax avoidance. However, the regulation is not significant in moderating the relationship between tax haven affiliation and corporate tax avoidance. The finding gives necessary information for policymakers to formulate a specific policy for the companies that own tax haven affiliation in order to prevent profit shifting by practicing dysfunctional intra-company transaction. Furthermore, this study enriches the literature on the importance of government regulation as external monitoring tool that support tax avoidance theory.
Keywords: 650; CbCR; government regulation; tax avoidance; tax haven; transfer pricing